Pilot Study of the Delivery of Microcollimated Pars Plana External Beam Radiation in Porcine Eyes: 270-Day Analysis. (11th July 2012) - Singh, Rishi P.; Shusterman, E. Mark; Moshfeghi, Darius; Danis, Ronald; Gertner, Michael
Abstract : Objective . To determine the dose response and toxicity threshold of micro-collimated X-rays delivered to porcine maculae by a stereotactic radiosurgical system after 270 days. Methods . Twelve eyes of six Yucatan mini-swine were randomized to receive up to 90 Gy to the retina, using an office-based trans-pars plana delivery system. To determine the safety profile of this radiation delivery, ophthalmic examination, fundus photography, fluorescein angiography (FA), and spectral domain optical coherence tomography (SD-OCT) were obtained at multiple time points up to 270 days post treatment. Results . No abnormalities were noted on external examination. Cataracts were noted in 4 of 12 eyes. Dose and time-dependent changes were noted on fundus examination, FA, ICG and SD-OCT. No significant abnormalities were seen in the control, 16 Gy or 24 Gy groups using any modality. Histopathology revealed a dose response effect with no discernable lesions in the 16 Gy group. Conclusion . The X-ray delivery system precisely targets the porcine retina in vivo with little effect on surrounding structures. No ophthalmic or intracranial adverse effects were noted at clinically relevant doses at 270 days following radiation delivery.